PEMBERDAYAAN MASYARAKAT DALAM PROGRAM PUSPAGA DIKELURAHAN SIDODADI KECAMATAN SIMOKERTO SURABAYA - Tiara Rizka Alfiana; Ilmi Usrotin Choiriyah (Halu Oleo University, 2024)
The purpose of this research is to increase knowledge about the protection of children and their families and the importance of utilizing government facilities for community empowerment. The type of research used was descriptive with a qualitative approach and applied a purposive sampling method to select informants, including the head of RW 05, Sidodadi village staff, Puspaga facilitators, and guardians of SMP Negeri 41 Surabaya students. Data were collected through observation, interviews, and documentation. Community Empowerment in RW 05 Sidodadi Village is measured using indicators of planned and collective action, improving people's lives, prioritizing vulnerable or disadvantaged groups and supporting capacity-building programs according to Hasibuan. The results showed that there were three indicators that were considered very well implemented and even sustainable until now and there was one indicator that was still considered insufficient due to the lack of community participation in utilizing the facilities that had been provided by the Surabaya Office of Women's Empowerment and Child Protection and Population Control and Family Planning (DP3APPKB) through Puspaga facilitators who were distributed in several villages in Surabaya, East Java.